IMPLEMENTASI KITAB UNDANG-UNDANG HUKUM PIDANA NASIONAL 2023 DALAM PERSPEKTIF YURISPRUDENSI KASUS KORUPSI ANALISIS PUTUSAN MAHKAMAH AGUNG TAHUN 2024 - Ahmad Nurafendi; Siti Humulhaer; Agus Eko Setyawan; Eduardo Retno; Ronald Pasrah (CV. Lafadz Jaya, 2026)
The reform of Indonesia’s criminal law system through the Indonesian National Criminal Code 2023, which came into effect on 2 January 2026, marks a new era in criminal law enforcement in Indonesia. This study analyzes the implementation of the National Criminal Code within the jurisprudential context of corruption cases based on decisions issued by the Supreme Court of the Republic of Indonesia in 2024. Using a normative–empirical juridical research method, this study examines 1,623 corruption case decisions adjudicated by the Corruption Court throughout 2024, as well as Supreme Court cassation decisions that have obtained final and binding legal force. The findings indicate that a transformation in the paradigm of sentencing from a punishment-oriented approach toward one emphasizing restoration and protection has begun to emerge in judicial decisions, particularly in the interpretation of the element of “unlawfulness,” which has been expanded to include violations of administrative regulations and corporate board decisions. This study recommends harmonizing the interpretation of the elements of corruption offenses between the National Criminal Code and the anti-corruption legal framework to prevent disparities in judicial decisions and to ensure legal certainty in the enforcement of corruption law following the implementation of the National Criminal Code.